Geomorphological Effects of River Valleys Anthropogenic Transformations in the Perznica Catchment During the Last 200 Years (Drawsko Lakeland, Parsęta River Basin) - Szpikowski, Józef (Quaestiones Geographicae, 2011)
The studies on geomorphological aspects of environmental changes in the river valleys were part of the work carried out under the diagnosis of anthropogenic transformation of the relief of the Perznica basin (West Pomerania, Drawsko Lakeland). Human interference in the river valleys and anthropogenic changes in the natural hydrological systems in the Perznica catchment influenced the transformation of the relief and the intensity of morphogenetic processes. Numerous anthropogenic landforms were formed, including embankments, dams, dykes along the canals, ditches and canals, reservoirs basins, and peat excavations. The drainage resulted in an intensification of the river erosion, straightening, shortening and increase of the river gradient, as well as the increase of quantity of the suspended matter leaving the catchments. An increase of anthropogenic denudation on agricultural lands, due to the entering of the crops grown on drained depressions and valleys, led to the masking of the original relief with deluvial sediments and the formation and expansion of agricultural terraces on the edge of the fields.